Gel of sandfish (Holothuria scabra) extract prevented melanin elevation in UVB-exposed guinea pig (Cavia porcellus) skin - Dwindi Saptania; Wimpie Pangkahila; Anak Agung Gde Putra Wiraguna (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Introduction: Hyperpigmentation is a condition of increasing melanin production in the skin due to UV light exposure. Sandfish (Holothuria scabra) contains phenol, quercetin, saponins, tannins, flavonoids and antioxidants such as vitamin C and others that have the potential anti-melanogenesis effects. The purpose of this study was to prove that topical administration of 40% sandfish (Holothuria scabra) extract gel prevented melanin elevation in UVB-exposed guinea pig (Cavia porcellus) skin. Methods: This study used a randomized post-test only group design by using of 36 guinea pigs. Guinea pigs were then divided into two groups. The control group were 18 guinea pigs exposed to UVB rays and treated with placebo gel base (P0). The treatment group were 18 guinea pigs exposed to UVB rays and treated with 40% sandfish extract gel. The back skin exposed to UVB rays, was cleaned from fur and swabbed with 70% alcohol. After that a punch-biopsy was carried out in the area and histopathological preparations were made. The amount of melanin was examined using Masson-Fontana staining. Results: The results showed that the average amount of melanin in the control group was 18.11± 1.11%, while the average amount of melanin in the treatment group was 1.82 ± 0.72%. Comparative analysis using independent T- test showed that the value of p was <0.001 means that there were significant differences between the control group and the treatment group. Conclusion: The administration of 40% sandfish (Holothuria scabra) extract gel prevented melanin elevation in UVB-exposed guinea pig (Cavia porcellus) skin.